Pain and sleep quality in children with non‐vascular Ehlers–Danlos syndromes. Issue 9 (4th September 2018) - Muriello, Michael; Clemens, Julia L.; Mu, Weiyi; Tran, Phuong T.; Rowe, Peter C.; Smith, Christy H.; Francomano, Clair; Bodurtha, Joann; Kline, Antonie D.
Abstract : The objective of this study was to explore the factors contributing to quality of life in pediatric patients with non‐vascular Ehlers–Danlos syndromes (EDS). Data were analyzed on 41 children with a diagnosis of non‐vascular EDS from the de‐identified data available from the National Institute on Aging (NIA) study of heritable disorders of connective tissue. Children under age 19 years were seen as part of a long‐term evaluation project from 2003 to 2013 on a larger natural history of patients with heritable disorders of connective tissue. Data collected included medical history, physical examination findings, diagnostic study results, and responses on validated questionnaires. We reviewed a sub‐cohort of children with a diagnosis of non‐vascular EDS and explored pain severity and interference via the Brief Pain Inventory, and sleep quality via the Pittsburgh Sleep Quality Index. Pain severity had a strong correlation with pain interference, and both were similar to other disorders that include chronic pain reported in the literature. Sleep quality did not correlate with pain severity or interference, but all patients had poor sleep quality in comparison to historical controls. We conclude that pain and sleep are significant issues in the pediatric non‐vascular EDS population, and future research may be directed toward these issues.